Promotion of skin fibroblasts collagen synthesis by polydioxanone mats combined with concentrated growth factor extracts. (October 2019) - Yue, Haiqiong; Zhou, Libin; Zou, Rui; Li, Zhicong; Liao, Ting; Yan, Jing; Zhou, Yang; Yang, Mi; Piao, Zhengguo
The purpose of this study was to combine polydioxanone and concentrated growth factor extracts to enhance the stimulation of fibroblast collagen synthesis by polydioxanone in facial plastic. In this experiment, polydioxanone was prepared as a nanoscale bioresorbable scaffold by electrospinning. The PDO-CGF mat was prepared by loading the concentrated growth factor extract onto the polydioxanone mat by lyophilization after soaking. The diameter of the mat fibers was observed by scanning electron microscopy, and the mechanical properties, biocompatibility and cytotoxicity of the material were analyzed. The release rate of transforming growth factor-beat1 (TGF-β1) in the PDO-CGF mat was evaluated by enzyme-linked immunosorbent assay (ELISA), and the amount of collagen synthesis was evaluated by real-time polymerase chain reaction (RT-PCR) and immunofluorescence. The results showed that the PDO-CGF mat had a nanometer-scale fiber diameter and an elastic modulus similar to skin and was able to pull during cell contraction. The PDO-CGF mat showed good biocompatibility, and the appropriate concentration of the PDO-CGF mat can significantly promote cell proliferation. ELISA showed that the PDO-CGF mat stably and continuously released TGF-β1. RT-PCR and immunofluorescence staining showed that the PDO-CGF mat stimulated fibroblasts to synthesize type I and type III collagen. These results indicate that a suitable concentration of the PDO-CGF mat can better promote the synthesis of collagen by fibroblasts.